The Implementation of Task-Based Language Teaching on Writing Descriptive Text - An Nida Nur Azizah; Kusrin Kusrin; Abdul Kodir Al-Baekani (Universitas Pendidikan Mandalika, 2021)
Students' responses to the implementation of task-based language teaching in the writing learning process and the implementation of task-based language teaching in the writing of descriptive text are the focus of this study. The research design used in this study is the case study. The participants that participated in the study were in the tenth grade of a vocational high school. There were three male and two female participants in this study. In addition, research utilizes observation, interviews, and documentation to gather data for the studies. There are three diplomas in the framework for task-based learning such as pre-task, task cycle, and language focus. As shown in the findings of this study, task-based language teaching has an influence on students' learning, particularly in regards to writing descriptive text. Students become active and task-based language teaching also influences students to involve a high level of creativity, students are required to think critically and be responsive. However, Students find it difficult with the tasks that have been assigned because it believes writing to be difficult and there are aspects of writing that weren't well understood.